Anna Karenina - Bevan, Tim.; Fellner, Eric.; Webster, Paul, 1952 September 19-; Stoppard, Tom.; Wright, Joe, 1972-; Knightley, Keira, 1985-; Law, Jude, 1972-; Taylor-Johnson, Aaron, 1990-; Gleeson, Domhnall, 1983-; Vikander, Alicia, 1988-; Macdonald, Kelly, 1976-; Macfadyen, Matthew, 1974-; et al. (Universal City, Calif. : Universal Studios Home Entertainment, 2013)
When married woman Anna falls in love with a soldier, she is given an ultimatum by her husband, the Imperial minister, and must make a choice about following her heart and losing her son or staying in her current marriage.
Based on the novel by Leo Tolstoy.
Directory of photography, Seamus McGarvey ; editor, Melanie Ann Oliver ; music, Dario Marianelli ; production design, Sarah Greenwood.
Keira Knightley, Jude Law, Aaron Taylor-Johnson, Domhnall Gleeson, Alicia Vikander, Kelly MacDonald, Matthew MacFadyen, Ruth Wilson.
MPAA rating: R; for some sexuality and violence.
DVD; anamorphic widescreen (2.40:1); NTSC, region 1; dual layer; Dolby digital 5.1 surround sound.
English or Spanish dialogue; Spanish or French subtitles; English subtitles for the deaf and hard of hearing.
Keywords: Karenina, Anna (Fictitious character) -- Drama; Married women -- Russia -- Drama; Adultery -- Russia -- Drama; Brothers and sisters -- Russia -- Drama; Man-woman relationships -- Drama; Film adaptations; Romance films; Feature films; Fiction films; Films for the hearing impaired